2019
DOI: 10.1007/s11071-019-04889-8
|View full text |Cite
|
Sign up to set email alerts
|

On the global dynamics of connected vehicle systems

Abstract: In this contribution, heterogeneous connected vehicle systems, that include human-driven as well as connected automated vehicles, are investigated. The reaction time delay of human drivers as well as the communication and actuation delays of connected automated vehicles is incorporated in the model. Saturations due to the speed limit and limited acceleration capabilities of the vehicles are also taken into account. The arising nonlinear delayed system is studied using analytical and numerical bifurcation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In our previous work [37], we investigated a system of CAVs where saturation was included in the model. Although the purpose of that research was not to expose the effect of saturation, it was concluded that badly chosen parameters resulted in a so-called isola causing bistability, where multiple solutions coexist, which could be improved by connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [37], we investigated a system of CAVs where saturation was included in the model. Although the purpose of that research was not to expose the effect of saturation, it was concluded that badly chosen parameters resulted in a so-called isola causing bistability, where multiple solutions coexist, which could be improved by connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a large corpus of studies has shown the connection of neural synchronization of brain areas with cognition 6 , animal locomotion is controlled to some extent by central pattern generators that impose a given gait by exploiting synchronous clusters of neurons 7 9 , and connected vehicle systems often give rise to CS 10 . The study of CS is therefore relevant to analyze and control natural (ecological, immune, neural, and cellular) 11 and artificial 12 14 systems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a large corpus of studies has shown the connection of neural synchronization of brain areas with cognition [6], animal locomotion is controlled to some extent by central pattern generators that impose a given gait by exploiting synchronous clusters of neurons [7,8,9], and connected vehicle systems often give rise to CS [10]. The study of CS is therefore relevant to analyze and control natural (ecological, immune, neural, and cellular) [11] and artificial [12,13,14]…”
Section: Introductionmentioning
confidence: 99%